PENGARUH KESEHATAN BANK TERHADAP TINGKAT INKLUSI KEUANGAN PADA BANK BNI KOTA GUNUNGSITOLI HENCE ANYCOLONY HUMENDRU - Humendru, Hence Anycolony; Harefa, Idarni; Bate’, Maria M; Bu’ulolo, Nanny (Fakultas Keguruan dan Ilmu Pendidikan, Universitas HKBP Nommensen, 2024)
The aim of this research is to examine the effect of bank health on the level of financial inclusion. This research uses sample collection techniques by distributing questionnaires. The research sample is customers of PT. Bank Negara Indonesia, Gunungsitoli city, was screened based on certain criteria or a purposive sampling technique, totaling 100 respondents. SMART-PLS is used as an analytical tool to test research hypotheses. The research results obtained were that there was a positive and significant influence on the research entitled